Effect of Corporate Financial Hedging, Risk Governance, Corporate Governance, Tax Avoidance on Firm value - Silva Wulandari; Susanti SE MM; Shella Rosananda; Amaliya Dinda Damara; Putu Monica Sari; Yesi Eka Evri Yanti; Gilang Ramadan (Proceeding International Conference on Information Technology and Business, 2022)
This research was conducted by looking at the phenomenon of recession that is predicted to occur in 2023 and the consideration of Covid-19 cases that have devastated the economy in the country for several years. There are many companies that feel disadvantaged and a sharp decline in the value of their companies. To increase company value, company owners improve company performance by conducting Corporate Financial Hedging, Risk Governance, Corporate Governance, Tax Avoidance. So that the purpose of this study was formed, namely to determine the influence of Corporate Financial Hedging, Risk Governance, Corporate Governance, Tax Avoidance on the value of Firms. The analysis method is descriptive statistical and Multiple Regression analysis.Keywords: corporate financial hedging, risk governance, corporate governance, tax avoidance, firm value